An unusual case of weight loss - Dr B Abhilash Nair; Dr V Padma; Dr Murugaraj M (International Journal of Pharma and Bio Sciences, 2020)
The extra pulmonary TB involves 11-16% of all TB patients, out of which 3-4% belong to abdominal TB. Abdominal TB is the 6th most common type of extra pulmonary TB. It includes the involvement of GI tract, lymph nodes, peritoneum and/or solid organs. In this article, we present a case of TB Abdomen in a 21-year-old male who presented to General Medicine outpatient department (Sree Balaji Medical College & Hospital) with only weight loss, loss of appetite and nausea as complaint. There were no lung signs or any others signs which could suggest or hint about tuberculosis. There was no history of contacts with any TB individual. It was initially ruled out but later on further examination, we did an USG which showed mild ascites. On analysis of the ascitic fluid, we could diagnose him to have tuberculosis. He was started on anti-tubercular treatment and managed medically without any surgery. One of the commonest features of an infectious disease like TB is fever, which if absent we tend to rule out the disease. Thus, it is important for us clinicians to be more vigilant as even though we rule out a diagnosis, it may on later stages be identified on careful examination and investigation. Our hospital had a similar case where in the patient presented with vague symptoms of diarrhoea and Malena and was later diagnosed as TB stomach and was also managed medically.